Anoda Pb dan Gel Elektrolit Untuk Propulsi Kapal Selam - Hens Saputra; Mochamad Rosjidi; Abdul Ghofar; Murbantan Tandirerung; Mochammad Ismail; Dorit Bayu Islam Nurwantoro (BRIN, 2017)
Battery is the most important component in the sub marine energy system. Up to now, majority of the sub marine are still using lead acid battery as the power source or propulsion, due to more safe in application as very high capacity of single cell (i.e. 10.000 – 15.000 Ah). The drawbacks of aqueous based battery, which utilize liquid electrolyte, are because of having produced the hydrogen gas during charging process, in which it caused the electrolyte solution to become dry and reduced the performance of battery. In addition that the hydrogen gas generated in the sub marine was dangerous. Therefore, the aim of this research is how to reduce or eliminate of those drawbacks by modifying kind of the liquid electrolyte by using gel electrolyte. The gel electrolyte was synthesized to reduce the evaporation of electrolyte and to avoid the leaking when submarine maneuver. The gel electrolyte was made by using inorganic nanoporous MCM-41. It was synthesized by hydrothermal method, using Tetraethylortosilicate (TEOS) as silica sources, Cethyltrimethylammonium bromide (CTAB) as organic template and H2SO4 as catalyst. The MCM-41 lead acid battery gave a result of OCV ca. 2,1 V.